2015
DOI: 10.1016/j.prevetmed.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Preventative services offered by veterinarians on sheep farms in England and Wales: Opinions and drivers for proactive flock health planning

Abstract: Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work of researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable the material made available in WRAP has been checked for eligibility before being made available.Copies of full items can be used for personal research or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…There are many examples of the divergence in views between sheep farmers and veterinarians (Kaler and Green 2013, Stubbings 2014, Bellet and others 2015), and clearly the resolution of these misunderstandings is essential to the building of successful flock health planning relationships. It has been suggested that greater success might be achieved by the veterinarian who focuses first on outcomes, for example, lamb growth rates and sales patterns, rather than the problems, such as anthelmintic resistance (Stubbings 2014).…”
Section: Barriers To the Vet/farmer Working Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many examples of the divergence in views between sheep farmers and veterinarians (Kaler and Green 2013, Stubbings 2014, Bellet and others 2015), and clearly the resolution of these misunderstandings is essential to the building of successful flock health planning relationships. It has been suggested that greater success might be achieved by the veterinarian who focuses first on outcomes, for example, lamb growth rates and sales patterns, rather than the problems, such as anthelmintic resistance (Stubbings 2014).…”
Section: Barriers To the Vet/farmer Working Relationshipmentioning
confidence: 99%
“…Recent research suggests that many veterinarians do not have much contact with their sheep farmer clients, as they do not believe themselves to be sufficiently knowledgeable or expert enough to be proactive and they do not believe that farmers will pay for their services (Bellet and others 2015). …”
Section: Barriers To the Vet/farmer Working Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for veterinarians not being more involved might be due to the veterinarians' and/or the farmers' perceptions and beliefs. A study highlighted that the proportion of time a veterinarian proactively spends in an advisory role with regard to preventative measures on a farm might depend on their required skill and motivation level, as well as whether counseling was seen as an income opportunity by the veterinarians, and if the farmers sought counseling [80]. In a survey of British farmers, inconsistent service, high turnover and a lack of expertise of sheep farming and concerns about independence of the advice given, were identified as barriers against the proactive use of veterinarians in sheep flock health management [81].…”
Section: Discussionmentioning
confidence: 99%
“…However, some sheep farmers have seen the benefit of regular veterinary involvement, and suggested that a proactive vet might work with a group of farmers of smaller flocks to reduce the veterinary cost per ewe (Kaler and Green 2013). In a response to these findings and the challenge to all UK sheep vets to maximise their ‘motivation, capability and opportunity’ (Reader 2014, Bellet and others 2015), the concept of a ‘flock health club’ was launched.…”
mentioning
confidence: 99%